2015
DOI: 10.1186/s12882-015-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between 24-hour blood pressure variability and chronic kidney disease: a cross-sectional analysis of African Americans participating in the Jackson heart study

Abstract: BackgroundStudies suggest 24-h blood pressure (BP) variability has prognostic value for cardiovascular disease. Several factors associated with high 24-h BP variability are also common among individuals with chronic kidney disease (CKD). We hypothesized 24-h BP variability would be higher for individuals with versus without CKD.MethodsWe analyzed 1,022 Jackson Heart Study participants who underwent ambulatory blood pressure monitoring (ABPM). Twenty-four hour BP variability was defined by two metrics: day-nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 26 publications
5
21
1
2
Order By: Relevance
“…The question of whether BPV causes CKD or CKD worsens BPV has been raised . The Jackson Heart Study showed that patients with CKD had higher BPV compared to those without CKD . Our study also showed that those with CKD at the end of 15 years have higher BPV compared to those without CKD.…”
Section: Discussionsupporting
confidence: 58%
“…The question of whether BPV causes CKD or CKD worsens BPV has been raised . The Jackson Heart Study showed that patients with CKD had higher BPV compared to those without CKD . Our study also showed that those with CKD at the end of 15 years have higher BPV compared to those without CKD.…”
Section: Discussionsupporting
confidence: 58%
“…We could not confirm that eGFR was associated with neither diurnal nor nocturnal BPV as shown by Tanner and coworkers [25]. They demonstrated that in a large sample of patients with CKD, BPV defined by day-night standard deviation and average real variability, was higher among participants with versus without CKD.…”
Section: Discussioncontrasting
confidence: 52%
“…CKD is associated with increased BP variability partly due to arterial stiffness [24]. Greater BP variability is associated with increased risk of hemorrhagic stroke in stage 3–4 CKD patients [25] and is a strong predictor of mortality in hemodialysis patients [26].…”
Section: Blood Pressure Variabilitymentioning
confidence: 99%